Indonesia’s Transition Toward Digital Twin in Smart Cities Development: An Integrative Review - Mombang Sihite; Aisyah Pia Asrunputri (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Indonesia's rapid urbanization, particularly in megacities like Jakarta, requires innovative solutions for optimizing urban infrastructure and sustainability. Digital Twin (DT) technology presents a promising approach to improving energy efficiency in smart buildings and advancing the smart city agenda. However, challenges in infrastructure, workforce skills, and regulatory support hinder its implementation. Objective: This study reviews the application of DT technologies in Indonesia's smart city development, focusing on energy efficiency in smart buildings. It explores DT adoption, identifies barriers, and proposes strategies for overcoming these challenges. Methods: An integrative review following PRISMA guidelines was conducted, analyzing 260 peer-reviewed articles published from 2002 to 2025. The review examined global trends, policy alignment, DT applications, enabling technologies, and barriers in Indonesia. Finding: DT technology is increasingly applied in smart building energy management in Indonesia, including smart building monitoring and dynamic construction projects. However, adoption is limited by challenges such as inadequate IoT infrastructure, high investment costs, fragmented governance, and lack of technical expertise. The Indonesian government's 100 Smart Cities initiative offers a supportive policy framework for DT implementation. Conclusion:The study highlights the potential of DT to enhance energy efficiency and support sustainable urban development in Indonesia. It recommends addressing barriers through coordinated policies, investments in IoT infrastructure, and human capital development. Future research should focus on longitudinal studies and cross-city comparisons to evaluate DT's effectiveness in urban sustainability.